The Oxford handbook of Seventh-Day Adventism - Campbell, Michael W.; Chow, Christie Chui-Shan 1967-; Kaiser, Denis; Miller, Nicholas Patrick 1967-; Holland, David F. (Oxford handbooks online, 2024)
By the early twentieth century, the Adventist movement had spread around the globe, and had made cultural contributions to medical science, health foods, archaeology, and education. This handbook 39 original essays addressing many aspects of Adventism. Broad and comprehensive in scope, each chapter addresses the history, theology, and social aspects of Adventism, and maps the development of its most influential manifestation. Authors from around the world, and from both inside and outside the Adventist tradition, have come together to produce this authoritative work